Analisis Big Data Geomagnetik Dengan Metode Diferensiasi Sebagai Prekursor Gempa Lombok Tahun 2018 - Dwi Ratnasari; Helmy Amalia Ariesta; Teti Zubaidah; Bulkis Kanata; Made Sutha Yadnya; Paniran Paniran; Supriyatna Supriyatna (LPPM Universitas Mataram, 2021)
Lombok is an area with the highest geomagnetic anomaly in Indonesia (Zubaidah et al., 2014). From the end of July to the end of August 2018, Lombok experienced a series of fairly large earthquakes. Identification of geomagnetic signals, especially in the Ultra Low Frequency (ULF) spectrum, can be used as earthquake precursors (Saroso, 2010). Intermagnet IAGA (International Aeronomy Geomagnetic Association) is a network of international geomagnetic observatory stations that have large world geomagnetic data. Big data analysis is very important because very large information is needed in disaster mitigation. This study uses geomagnetic data per second for 24 hours from 28 August to 30 November 2018 taken from Kakadu (KDU) Australia and Nurul Bayan Station (NRB) Lombok. The analytical method used is Differentiation by calculating the F value (total magnetic field) for KDU and NRB, then look for the difference and analyze the pattern. The results found that there was an anomaly phenomenon of the Earth's magnetic field in Nurul Bayan Lombok which was detected for 17 days during October 2018.